2018
DOI: 10.14419/ijac.v6i2.11019
|View full text |Cite
|
Sign up to set email alerts
|

A semi-empirical estimation of ground and excited state dipole moments of zinc phthalocyanine from solvatochromic shift data

Abstract: A semi-empirical determination of ground and excited state dipole moments of zinc phthalocyanine (ZnPc) from solvatochromic shifts is hereby presented. The ratio of the excited- and ground-state dipole moments of ZnPc ( ) was estimated by a combination of the Bakshiev and the Kawski-Chamma-Viallet’s equations, while the difference in the excited- and ground-state dipole moments (Dm) was estimated usingthe molecular-microscopic solvent polarity parameters ( ), alongside the Stokes’ shifts (Dῡ) in the va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…( It is of interest to note that the values of g and e determined for ZnTBPc are significantly greater than those obtained for ZnPc (g=1.50D; e=3.12D) in an earlier work [19]. In ZnPc, it was suggested that the drop in symmetry from D4h to C4v in the molecule is responsible for its observed polarity.…”
Section: Ground-and Excited-state Dipole Moments Of Zntbpcmentioning
confidence: 70%
See 1 more Smart Citation
“…( It is of interest to note that the values of g and e determined for ZnTBPc are significantly greater than those obtained for ZnPc (g=1.50D; e=3.12D) in an earlier work [19]. In ZnPc, it was suggested that the drop in symmetry from D4h to C4v in the molecule is responsible for its observed polarity.…”
Section: Ground-and Excited-state Dipole Moments Of Zntbpcmentioning
confidence: 70%
“…However, literature is very scanty on the use of solvent-induced shifts for the determination of dipole moments of Pcs. In the present study, a semi -empirical estimation of the ground and excited-state dipole moments of 2(3)-tetra(tertbutylphenoxy)phthalocyaninato zinc(II) is presented using the solvatochromic shift method [18][19][20][21], which is based on the Onsager's reaction field theory [22].…”
Section: Introductionmentioning
confidence: 99%